Epidemiology and Impact of Abdominal Oblique Injuries in Major and Minor League Baseball. Issue 3 (7th March 2017) - Camp, Christopher L.; Conte, Stan; Cohen, Steven B.; Thompson, Matthew; D' Angelo, John; Nguyen, Joseph T.; Dines, Joshua S.
Background: Oblique injuries are known to be a common cause of time out of play for professional baseball players, and prior work has suggested that injury rates may be on the rise in Major League Baseball (MLB). Purpose: To better understand the current incidence of oblique injuries, determine their impact based on time out of play, and to identify common injury patterns that may guide future injury prevention programs. Study Design: Descriptive epidemiological study. Methods: Using the MLB Health and Injury Tracking System, all oblique injuries that resulted in time out of play in MLB and Minor League Baseball (MiLB) during the 2011 to 2015 seasons were identified. Player demographics such as age, position/role, and handedness were included. Injury-specific factors analyzed included the following: date of injury, timing during season, days missed, mechanism, side, treatment, and reinjury status. Results: A total of 996 oblique injuries occurred in 259 (26%) MLB and 737 (74%) MiLB players. Although the injury rate was steady in MiLB, the MLB injury rate declined ( P = .037). A total of 22, 064 days were missed at a mean rate of 4413 days per season and 22.2 days per injury. The majority of these occurred during batting (n = 455, 46%) or pitching (n = 348, 35%), with pitchers losing 5 days more per injury than batters ( P < .001). The leading side was injured in 77% of cases and took 5 days longer to recover from than trailing side injuries ( P = .009). Seventy-nine (7.9%) players received either a corticosteroid or platelet-rich plasma injection, and the mean recovery time was 11 days longer compared with those who did not receive an injection ( P < .001). Conclusion: Although the rate of abdominal oblique injuries is on the decline in MLB, this is not the case for MiLB, and these injuries continue to represent a significant source of time out of play in professional baseball. The vast majority of injuries occur on the lead side, and these injuries result in the greatest amount time out of play. The benefit of injections for the treatment of oblique injuries remains unknown.